2021
DOI: 10.1021/acsami.0c22933
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the Mg Alloy AZ31 Anodizing Process for Biodegradable Implants

Abstract: Coatings were grown on the AZ31 Mg alloy by a hard anodizing process in the hot glycerol phosphate-containing electrolyte. Anodizing conditions were optimized, maximizing corrosion resistance estimated by impedance measurements carried out in Hank’s solution at 37 °C. A post anodizing annealing treatment (350 °C for 24 h) allowed us to further enhance the corrosion resistance of the coatings mainly containing magnesium phosphate according to energy-dispersive X-ray spectroscopy and Raman analyses. Gravimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…144 Zaffora et al verified that MgP coatings that had grown on the AZ31 Mg alloy by a hard anodizing process were biocompatible and could enhance the corrosion resistance of the AZ31 Mg alloy. 145 Similarly, Ma et al also confirmed that MgP coating not only significantly decreased the degradation rate of the AZ31 alloy, but also promoted the cell proliferation. 146 Therefore, MgP coatings are a promising candidate for clinical applications.…”
Section: Magnesium Phosphate Coatingsmentioning
confidence: 85%
“…144 Zaffora et al verified that MgP coatings that had grown on the AZ31 Mg alloy by a hard anodizing process were biocompatible and could enhance the corrosion resistance of the AZ31 Mg alloy. 145 Similarly, Ma et al also confirmed that MgP coating not only significantly decreased the degradation rate of the AZ31 alloy, but also promoted the cell proliferation. 146 Therefore, MgP coatings are a promising candidate for clinical applications.…”
Section: Magnesium Phosphate Coatingsmentioning
confidence: 85%
“…[1][2][3] The most concerning problem is still its excessive degradation rate, causing biocompatibility issues in the human body. [4][5][6] Coating technology is one of the most popular approaches for improving the performance of magnesium alloys. Common polymers such as synthetic polymers (polylactic acid (PLA), [7] poly (latic-co-glycolic) acid (PLGA), [8] and polycaprolactone (PCL) [9] are inferior in mechanical Indeed, fragile adhesion at the organic coating/metal substrate interface is mainly caused by poor hydrophilicity and insufficient functional groups on magnesium surfaces due to the naturally formed oxide layer (magnesium oxide, magnesium hydroxide, magnesium carbonate) in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] The most concerning problem is still its excessive degradation rate, causing biocompatibility issues in the human body. [ 4–6 ] Coating technology is one of the most popular approaches for improving the performance of magnesium alloys. Common polymers such as synthetic polymers (polylactic acid (PLA), [ 7 ] poly (latic‐ co ‐glycolic) acid (PLGA), [ 8 ] and polycaprolactone (PCL) [ 9 ] are inferior in mechanical properties, corrosion resistance, and especially biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…These coatings enhance bonding strength between copper and various polymers [11,12]. The anodizing method has been adopted to modify AZ31 Mg alloys to enhance corrosion resistance and biocompatibility, especially used for biomedical devices [13]. Electroless nickel coating technique has also been adopted to produce coating on the substrate surface to improve various properties of the base material [14].…”
Section: Introductionmentioning
confidence: 99%